Analisis Strategi Pembiayaan Usaha Mikro dan Kecil Melalui Dana Bergulir pada Lembaga Pengelola Dana Bergulir - Trisnojuwono, Adi; Hubeis, Aida Vitayala S; Cahyadi, Eko Ruddy (Institut Pertanian Bogor, 2017)
The Ministry of Cooperatives and SMEs established a Revolving Fund Management Institution for the Micro, Small and Medium Enterprises (LPDB-KUMKM) in order to realize the mandate of Law No. 20 of 2008, with the aim of managing and developing revolving funds for the Micro, Small and Medium Enterprises professionally and accountably. The increasing number of Revolving Fund distribution services and the decreasing level of loan classification in the current category encouraged the need to evaluate loan or financing distribution through (1) analysis of factors affecting LPDB-KUMKM revolving fund performance and (2) to formulate effective strategies to improve the performance of revolving fund for the Micro, Small and Medium Enterprises. The method used in this research are, descriptive analysis, logistic regression analysis and AHP. The analysis result shows the significant factors that influence the performance of the revolving fund efficiency are financing schemes (conventional or syariah schemes), loan plafond and business establishment period. The proposed strategies that can be considered in improving LPDB-KUMKM's performance take into account the increasing effectiveness of loan or financing disbursement, which includes loan or financing channels and factors that significantly influence the success of return.